The Hemoptysis and the Subclavian Artery Pseudoaneurysm due to a Fishbone Injury: A Case Report. Issue 42 (October 2015) - Lee, Yong Jik; Park, Chang-Ryul; Kim, Jeong Won; Kim, Yun Seok; Hwang, Jae Cheol; Seo, Kwang Won; Jung, Jong-Pil
Abstract : Abstract: Ingestion of a foreign body is a common cause of esophageal injury, but hemoptysis is a rare manifestation of the esophageal penetration by a swallowed foreign body. The swallowing of a fishbone is hard to diagnose and the definite diagnosis is usually made during surgery. We describe the case of a 50-year-old man with direct injury to the lung parenchyma, the azygos vein, and the subclavian artery pseudoaneurysm due to a fishbone penetration from the upper esophagus into the lung. To our knowledge, this is the first case report that we know of in which a swallowed foreign body that penetrated from the upper esophagus into the lung caused vascular injuries and lung damage and it was solved by minimally invasive surgery and an endovascular stent. We successfully diagnosed and treated a case with the migration of the fishbone from the upper esophagus into the lung. A contrast-enhanced computed tomography (CT) scan is recommended to clarify the fact of vascular injury before surgery. Thoracoscopic operation (VATS) combined with endovascular treatment could be a safer and a more feasible treatment option in this rare condition.